Design Conseptual of Hybrid Project Based Learning-PEPPER in Computer Networking Learning - Haryadi, Rudi; Abdullah, Ade Gafar (Faculty of Technological and Vocational Education-Universitas Pendidikan Indonesia, 2015)
Learning of vocational school learning should be able to prepare students who have qualified skills to fit the demands of the realistic activity of industry. Professional activities within the workplace should be integrated completed the learning process in the classroom, through pedagogical model design that facilitates learning in order to build students who have the ability to work in accordance with the demands from the industry. Development of model design has been done through collaboration models Project-based learning and PEPPER model through a mix method research. This research resulted a pedagogical syntax of learning model's tools with characteristic's industrial standard, which quantitatively tested in learning of Computer Network, so that the application of this model can improve the presumption of vocational school quality through graduate's quality.